An organometal halide perovskite supported Pt single-atom photocatalyst for H2 evolution. Issue 3 (8th February 2022) - Wu, Yaqiang; Wu, Qian; Zhang, Qianqian; Lou, Zaizhu; Liu, Kefeng; Ma, Yandong; Wang, Zeyan; Zheng, Zhaoke; Cheng, Hefeng; Liu, Yuanyuan; Dai, Ying; Huang, Baibiao; et al.
Abstract : An organometal halide perovskite supported Pt single-atom photocatalyst is developed for efficient H2 evolution with a superb STH of 4.50%. Abstract : A supported single-atom catalyst provides an opportunity to make full use of noble metals with optimized efficiency and minimal amount. For photocatalytic applications, organometal halide perovskites are greatly ideal candidates as substrate materials for supporting single-atom catalysts because of their excellent properties and remarkable performance in the photoelectric area. However, atomically dispersing noble metals on organometal halide perovskites stably and firmly remains a challenge. Here, we realize the preparation of single-atom Pt immobilized on FAPbBr3− x I x (FA = CH(NH2 )2 ) perovskite substrates through self-adsorption and photo-reduction, as a superb hydrogen evolution photocatalyst for hydrohalic acid splitting. Theoretical and experimental investigations show that Pt atoms are immobilized individually and coordinated with surface halide anions by replacing formamidinium groups. The developed Pt/FAPbBr3− x I x (FAPbBr3− x I x loaded with Pt single-atoms) sample shows an enhanced photocatalytic H2 evolution activity of 682.6 μmol h −1 (100 mg) under simulated sunlight irradiation (AM1.5G, 100 mW cm −2, irradiation area of π cm 2 ), with an exciting STH (solar-to-hydrogen efficiency) of 4.50%. This work provides a platform that facilitates the synthetic strategy for designing a halide ion coordinated single-atom catalyst, enhancing the photocatalytic performance of perovskite materials, and extending the boundary of the conventional supporting substrate and research fields for single-atom catalysts.